(untitled) - Cohan, Phuli (Hoboken, N.J, 2008)
A female doctor who has spent more than two decades studying the relationship between hormones and menopause presents a safe, effective program for using natural and bioidentical hormones to combat hot flashes, insomnia, mood swings, and many other symptoms linked to menopause-related hormone imbalances. Combining traditions of Chinese medicine with the latest Western developments and discoveries, this easy-to-follow ten-step program helps you create a personalized course of treatment using supplements, herbs, natural and bio-identical hormones, and diet to enhance both safety and hormone effectiveness
Keywords: Hormone therapy,Endocrine gynecology,Rejuvenation; Popular works.,Popular works